CONCENTRATION OF HEAVY METALS IN PADDY SOILS AND ITS ACCUMULATION IN RICE GRAINS IN GASHUA, BADE LOCAL GOVERNMENT AREA, YOBE STATE, NIGERIA - Yila, Eliazar; Shafiu, Adamu; Onyia, Emmanuel Chigozirim; Godly, Chessed; Philips, Vandi; Daskum, Adullahi; Sakiyo, David; Wandiyahel, Titus (FUDMA Journal of Sciences, 2025)
The study aimed to determine the concentration of heavy metals in paddy soil and rice grains in Gashua, Bade local government area, Yobe state. Three sampling stations were selected, Station A (Jabulle), B (Bayan Gada) and C (layin Kwata). Soil samples and paddy rice grains were collected in triplicates. The quantities of heavy metals (Pb, Cr, Cd, Cu, As, and Ni) were determined in both the soil and paddy rice grains. The mean values of metals found in soil (mg/kg) in station A were as follows: Lead (3.13±0.137), Chromium (2.82±0.65), Cadmium (1.37±0.14), Copper (5.86±0.63), Arsenic (1.33±0.14) and Nickel (2.93±0.32), while station B: Lead (6.10±1.027), Chromium (2.94±0.17), Cadmium (2.67±0.49), Copper (9.38±1.34), Arsenic (2.35±0.10) and Nickel (4.69±0.67) and station C: Lead (1.85± 0.41), Chromium (2.38±0.14), Cadmium (1.49±0.44), Copper (4.58±0.37), Arsenic (1.04±0.08) and Nickel (2.29±0.18). Heavy metals were detected in the order Cu > Pb > Ni > Cr > Cd > As and as > Cd > Cr > Ni > Pb > Cu > in the soil and rice samples, respectively. The mean physico-chemical value obtained in station A were pH (6.7 ± 0.21), Electrical Conductivity (504±430.62), Organic Carbon (3.4±0.66) and Moisture (11.10±1.08), while for station B: pH (6.9±0.31), Electrical Conductivity (545±97.04), Organic Carbon (2.34±1.29) and Moisture (11.49±1.66) and station C: pH (6.4±0.2), Electrical Conductivity (824±27.22), Organic Carbon (2.43±0.37) and Moisture (8.94±1.30). From this analysis, it was observed that the detected concentrations of Cu, Cd, Cr, and As were higher than the WHO/FAO recommended maximum tolerance values.